SUPPORTING ONLINE LEARNING IN THE COUNTRYSIDE (American Journal of Pedagogical and Educational Research, 2023)
This article describes the effectiveness and challenges of online learning in rural areas. The findings of the study reveal that e-learning is a huge challenge for rural schools with a lack of online learning resources, skilled teachers, and so on.